Game Based Education : Motorcycle Repair Game - Wira Wangsawijaya; Sumenge Tangkawarouw Godion Kaunang; Virginia Tulengan (Universitas Sam Ratulangi, 2020)
Motorbikes are currently one of the most popular means of transportation among the public. Judging from the relatively affordable price of motorbike transportation, motorbikes are also easier and more practical than other means of transportation to support all activities. However, some motorcycle users experience problems when servicing and maintaining their vehicles. This study aims to develop a motorcycle repair game that will become a medium for introducing motorcycle spare parts. Using the protoyping method, namely, Needs Analysis to find out data needs and user needs, Design to make storyboards and use cases, and Testing to test black box software and graphical testing. From the results of research evaluation can produce prototypes of Motor Repair Games that can help introduce about motorcycle parts.Games made using pixel art have never been made and published by other parties, so this game is something new.